The Ethics of Artificially Intelligent Sexbots : A Philosophical Investigation into the Ethical Conditions for Human-Sexbot Interaction - Ruttkamp-Bloem, Emma (University of Pretoria, 2021)
Dissertation (MPhil)--University of Pretoria, 2020.